Y2K options and the liquidity premium in treasury bond markets - Suresh Sundaresan; Zhenyu Wang (Federal Reserve Bank of New York, 2006)
Financial institutions around the world expected the millennium date change (Y2K) to cause an aggregate liquidity shortage. Responding to concerns about this liquidity shortage, the Federal Reserve Bank of New York auctioned Y2K options to primary dealers. The options gave the dealers the right to borrow from the Fed at a predetermined interest rate. The implied volatilities of Y2K options and the aggressiveness of demand for these instruments reveal that the Fed's action eased the fears of bond dealers, contributing to a drop in the liquidity premium of Treasurysecurities. Our analysis shows the link between the microstructure of government debt prices and the central bank's provision of liquidity. The use of Y2K options and their effect on the liquidity premium broadly conform to the economic theory and practice of the public provision of private liquidity.
Keywords: G1; G13; G18; 330; Y2K options; liquidity; Treasury bonds; Optionsgeschäft; Gesamtwirtschaftliche Liquidität; Schatzpapier; USA